2013
DOI: 10.1111/dme.12067
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the transition from paediatric to adult care among emerging adults with Type 1 diabetes

Abstract: Aims The goals of the study were to describe the transition of youth with Type 1 diabetes from paediatric to adult healthcare services, examine the link of this transition with self care and glycaemic control, and distinguish youth who received medical treatment from different physicians in terms of demographic and parent relationship variables. Methods Youth with Type 1 diabetes (n = 118) were enrolled in a prospective study that examined the transition from the paediatric to adult healthcare systems and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 26 publications
3
86
1
1
Order By: Relevance
“…There was some modest evidence that the cognitive adaptation index was linked to better glycemic control. Such a link would be extremely important as emerging adults are at risk for poor glycemic control when they move from the pediatric health care system to the adult health care system (48). …”
Section: Discussionmentioning
confidence: 99%
“…There was some modest evidence that the cognitive adaptation index was linked to better glycemic control. Such a link would be extremely important as emerging adults are at risk for poor glycemic control when they move from the pediatric health care system to the adult health care system (48). …”
Section: Discussionmentioning
confidence: 99%
“…A review by Lyons, Becker, and Helgeson suggests that young adults maintain stable or even improved glycemic control after the transfer to adult medical care [45]. However, other studies have demonstrated that premature transition to adult medical care is associated with poorer glycemic control [46] and that youth who remain in pediatric care early in young adulthood demonstrate better glycemic control as compared to young adults who transfer to adult care [47]. These data should be interpreted cautiously, as information about glycemic control in young adulthood may represent a biased sample of patients who present for medical care and have appropriate labs drawn.…”
Section: Transition To Adult Health Carementioning
confidence: 99%
“…Thus, for young adults, clinic attendance, rather than specific indicators of diabetes control, may represent a critical outcome to track [40, 45]. Young adults at risk for poor glycemic control or low rates of clinic attendance post-transfer to adult medical care may have lower income, live in areas with relatively low physician supply, or have a history of poor glycemic control [12, 46]. Assessing readiness for adult medical care and matching the transfer time with perceived readiness, when possible, may enhance outcomes in adult care.…”
Section: Transition To Adult Health Carementioning
confidence: 99%
“…Many young adults will find themselves responsible for making clinic appointments, refilling prescriptions, and finding and managing insurance on their own, often for the first time in their lives. Errors or omissions in diabetes management may therefore become more likely [55]. With new environments and responsibilities, emerging adults will likely have to continuously re-evaluate their plan for integrating T1D care into everyday activities.…”
Section: Emerging Adulthood: Taxed Efmentioning
confidence: 99%
“…When faced with a long-term goal, Barkley and Benton [55] recommend people create smaller steps toward the larger goal. For example, if an adult wishes to lower his A1c by 1 %, he can identify small, achievable behavioral steps to reach this goal (e.g., checking his BG one more time a day) and give himself small rewards for each small objective met (e.g., each week he successfully conducts one additional check per day).…”
Section: Adulthood: Plateau At the Peak Of Efmentioning
confidence: 99%